ANALISIS PENGENDALIAN KUALITAS STATISTIK GULA RAFINASI DENGAN PETA KENDALI MULTIVARIAT T-SQUARE (STUDI KASUS: PT. MAKASSAR TENE) - Kasse, Irwan; Erianti, Efita; Irwan, Muh. (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2020)
Sugar is a simple carbohydrate that is a source of energy. Sugar consumption in each country are different from Indonesia. Demand for sugar in Indonesia is always changing and increasing along with increasing of the population in Indonesia. If sugar consumption in Indonesia is Increasing, Sugar Production have to be increased. Of course, the company have to guarantee the quality of sugar. There are several factors that affect the quality of sugar. So, the company must always check the quality of sugar to be producted by considering these factors. Therefore, this research used multivariate T2 control chart method. This study aims to determine whether refined sugar products have been statistically controlled using multivariate T-Square control chart. The method used is the Statistical Quality Control method with multivariate T-Square control chart. The results of the study show that all refined sugar products have been statistically controlled by using multivariate T-Square control chart after making several revisions and can be a reference in the analysis control chart.